Synthesis, photophysical properties, and self-dimerization studies of 2-λ5-phosphaquinolin-2-ones. Issue 8 (1st April 2019) - Bard, Jeremy P.; Deng, Chun-Lin; Richardson, Hannah C.; Odulio, Jacob M.; Barker, Joshua E.; Zakharov, Lev N.; Cheong, Paul H.-Y.; Johnson, Darren W.; Haley, Michael M.
Abstract : Rationally designed phosphaquinolinone derivatives containing electron-donating and/or -withdrawing groups are reported, with dimerization constants up to 525 M −1 . Abstract : We have rationally designed and synthesized a library of phosphaquinolinone derivatives containing various electron-donating and -withdrawing groups on two positions of the scaffold. Distinct trends are observed between the substituents on R 1 and R 2 with both the photophysical properties of the molecules and their dimerization strengths. With withdrawing groups upon the scaffold, dimerization constants surpass 500 M −1 in H2 O-saturated CDCl3 . Computational studies on the dimeric structures corroborate the experimental findings.